Socio-Emotional Development of Women Who Are Pregnant Out of Wedlock - Prisilia Caroline keo; Marni Marni; Dian Lestari Anakaka; Mariana Dinah Ch. Lerik (Universitas Nusa Cendana, 2025)
Early marriage under age 19 in East Nusa Tenggara remains high, driven by low education, child-rearing practices, and economic vulnerability. This study aims to describe and analyze the socio-emotional development of women who have committed to early marriage due to out-of-wedlock pregnancy in Kupang City. This study uses a qualitative, descriptive approach. The informants consisted of five women who had an out-of-wedlock pregnancy and were married under the age of 19. The results of the study showed that women who experienced early marriage due to out-of-wedlock pregnancies faced emotional challenges in the form of shame, social rejection, and psychological pressure from the surrounding environment. However, family support and self-acceptance are essential factors that can strengthen their emotional resilience. This research emphasizes the importance of the role of social support in assisting women who experience this condition and the urgency of preventing early marriage through education and policy interventions.